Summary of the evidence of best practices for the prevention and treatment of embolism syndrome after TACE in primary liver cancer - Yao, Yanrong; Huang, Xi; Zhao, Chengsi; Wang, XiaoYan; Mi, Guangli; Liu, Jingli (Frontiers in Oncology, 2024)
Objective: To retrieve, evaluate, and summarize domestic and foreign evidence on the prevention and treatment of embolism syndrome following Transcatheter Arterial Chemoembolization (TACE) for primary liver cancer and to provide an evidence-based foundation for clinical practice. Methods: Utilizing the "6S" model, we conducted a systematic search of UpToDate, BMJ Best Practice, domestic and foreign guidelines, and related databases on the prevention and treatment of embolism syndrome following TACE for primary liver cancer. This search included clinical decision-making, guidelines, systematic reviews, evidence summaries, randomized controlled trials, and expert consensus. The search time frame extended from January 1, 2013, to May 1, 2023. Evidence was synthesized after an independent review of included studies by two investigators. Results: A total of 11 articles were included in the analysis, comprising 1 clinical decision-making article, 3 clinical guidelines, 6 expert consensus articles, and 1 randomized controlled trial. We summarized 31 pieces of evidence across three categories: preoperative preparation, intraoperative interventions, and postoperative symptom management. Conclusion: This study presents a comprehensive summary of the best available evidence on the prevention and treatment of embolism syndrome following TACE for primary liver cancer. These findings can serve as a valuable reference for clinical practitioners, enabling nurses to deliver individualized care based on the symptoms and specific needs of liver cancer patients.